2022
DOI: 10.4103/ija.ija_25_22
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the three-point cuff palpation technique in preventing endobronchial tube migration during positioning in robotic pelvic surgeries

Abstract: Background and Aims: During robotic pelvic surgeries, the shortening of endotracheal tube (ETT) tip-to-carina distance (D TC ) during pneumoperitoneum with 45° Trendelenburg position can result in endobronchial tube migration. In the three-point ETT cuff palpation (TPP) technique, maximal ETT cuff distension is felt over the tracheal segment located between the cricoid-thyroid membrane and suprasternal notch, which is likely to provide optimal placement. However, the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As part of the standard introduction to general anesthesia involves securing the airway by using the right-sized endotracheal tube (ET) tube, which should be properly inserted, and the position of the tube should be checked by auscultation, after which it should be properly taped and fixed, a high probability of the tube migrating into the unventilated lung and collapsing, causing hypoxia, is a possibility. A threepoint ET cuff palpation approach is easy to use, reliable, and successful in decreasing the chances of endobronchial tube movement during robotic pelvic surgery, according to a recently published study [9]. ET tube position should also be checked regularly.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the standard introduction to general anesthesia involves securing the airway by using the right-sized endotracheal tube (ET) tube, which should be properly inserted, and the position of the tube should be checked by auscultation, after which it should be properly taped and fixed, a high probability of the tube migrating into the unventilated lung and collapsing, causing hypoxia, is a possibility. A threepoint ET cuff palpation approach is easy to use, reliable, and successful in decreasing the chances of endobronchial tube movement during robotic pelvic surgery, according to a recently published study [9]. ET tube position should also be checked regularly.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study, the authors found that the three-point endotracheal tube cuff palpation technique is simple, reliable and effective in preventing endobronchial tube migration during robotic pelvic surgery. [ 14 ] Furthermore, tube placement should be checked frequently. Tidal volume should be maintained between 6 and 8 ml/kg with plateau pressure (P PLAT ) not exceeding 30 cm of H 2 O.…”
Section: Intraoperative Managementmentioning
confidence: 99%